2018
DOI: 10.1016/j.ijnss.2018.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of health-promoting behaviour among older adults with hypertension in Indonesia

Abstract: Objectives This study aimed to determine the predictors of health-promoting behaviour among older adults with hypertension in Bengkulu City, Bengkulu, Indonesia. Methods A cross-sectional study was conducted in 333 older adults with hypertension, who were selected using multistage sampling method. Data were obtained by face-to-face interview with structured questionnaires. The questionnaires used in this study included the Health-Promoting Lifestyle Profile II (HPLP II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
7
23
0
4
Order By: Relevance
“…In this study, participants with higher levels of self-efficacy were found to have higher levels of engagement in health-promoting behaviors, consistent with previous findings [ 7 , 44 ]. This indicates the necessity of providing a nursing intervention to improve the self-efficacy of elderly women with hypertension who must be encouraged to engage in health-promoting behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, participants with higher levels of self-efficacy were found to have higher levels of engagement in health-promoting behaviors, consistent with previous findings [ 7 , 44 ]. This indicates the necessity of providing a nursing intervention to improve the self-efficacy of elderly women with hypertension who must be encouraged to engage in health-promoting behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 22 cross-sectional studies included, ten were performed in Asia [ 22 , 24 , 27 , 31 , 33 , 36 , 37 , 40 – 42 ], three in the Middle East [ 23 , 25 , 32 ], five in the United States of America [ 26 , 28 , 29 , 37 , 43 ], two in Europe [ 30 , 39 ], one in Africa [ 34 ] and one in Australia [ 69 ]. All the studies involved adults, of which four [ 24 , 36 , 40 , 42 ] involved exclusively elderly adults aged 60 or older.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies involved adults, of which four [ 24 , 36 , 40 , 42 ] involved exclusively elderly adults aged 60 or older. Of the 22 studies, 13 studies [ 23 , 25 , 27 , 29 , 31 , 32 , 34 , 36 , 38 42 ] involved participants recruited from healthcare settings while eight [ 22 , 24 , 26 , 28 , 33 , 37 , 43 , 69 ] involved participants recruited from the community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization (WHO), noncommunicable diseases (NCDs), such as cardiovascular diseases, cancers, chronic respiratory diseases, and diabetes, account for 41 million deaths each year globally, and more than three-quarters of global NCD-related deaths occur in lowand middle-income countries [1]. Indonesia is one of the countries that has been facing a rapid increase in NCD-related deaths [2,3], and the prevalence of NCDs including obesity, hypertension, and diabetes in women is significantly higher than that in men [4][5][6][7][8]. The Indonesian Ministry of Health has developed NCDs control programs and launched several community health centers (Puskesmas) and health village posts for older adults (Posyandu Lansia) in the mid-2000s.…”
Section: Introductionmentioning
confidence: 99%